A Dynamic Halal Social Capital-Based Islamic Religious Education Learning Model for the Development of University Students' Digital Ethics - Mustofa, Taufik; Maulana, Rd. Muhamad Hilmi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the Dynamic Halal Social Capital-based Islamic Education learning model in fostering digital ethics among university students. This study uses a qualitative approach with a case study design conducted on undergraduate students of the Islamic Education Study Program at the Faculty of Islamic Studies, Singaperbangsa University, Karawang. Data were obtained from in-depth interviews with students and lecturers, observations of the learning process in the classroom, analysis of learning administration documents, and supported by questionnaire data to reinforce field findings. The data were analyzed using thematic analysis to identify learning patterns, forms of Dynamic Halal Social Capital integration, and their implications for the formation of students' digital ethics. The results showed that the Dynamic Halal Social Capital-based Islamic Education learning model, which integrates beliefs, Islamic norms, and academic social networks, is capable of fostering students' digital ethics through three main orientations, namely digital academic, religious, and digital social. This model is implemented through a participatory, reflective, and contextual learning approach, so that digital ethics is understood as a moral, social, and spiritual responsibility. This study provides a conceptual contribution by offering a framework for an Islamic Education learning model based on halal social capital, as well as an empirical contribution to the development of Islamic Education learning that is adaptive and relevant to the ethical challenges of the digital age.